DINAMIKA KLASIK PADA TUMBUKAN KOLINIER H2+H: tinjauan pada batas antara tumbukan reaktif dan tumbukan non-reaktif - Abdulkadir Martoprawiro, Muhamad
Chemists are becoming interested in studying natural phenomena in terms of molecular behavior. Chemical kinetics, as well as other chemistry fields, started from the macroscopic approach, and later entered into the microscopic approach. This investigation is a preliminary study to the microscopic aspects of this field, which will link the macroscopic and the microscopic kinetics. The first reaction which had been investigated was a simple reaction: H + Hz Â€ Hz + H. The aim of this investigation is to study the system\'s behavior at the border of the reactivity bands. It has been observed that a random discontinuity occures at these bands. The reaction system is observed classically and has been limited at colinier collisions. Potential Energy Surface (PES) was derived analitically from the Morse potential which interpolated to PES saddle point. The interpolation was conducted using coordinate which was used in bond-energy-bond-order approach. Particle trajectory at PES is derived numerically by integration of Hamilton\'s equation for the system. Turbo Pascal version 5.5 with object oriented programming is used as a computer programming language for solving the equation. Morse potential for Hz molecule is used with potential barier 9.8 kJ/mol (15.6 mhartree), Hz initial vibration energy 9.475 mhartree (ground state), and initial phase O. Calculation result shows that collision energy of 9.844 mhartree gives reaction, whilest collision energy of 9.843 mhartree gives no reaction. For the same collision energy, from furher calculations, reactivity of the collision depends on the initial phase of the Hz molecule vibration and initial separation. The research did not show a definit collision energy which is a border of the reactivity, although in the same orientation (colinier, in this case). The same collision energy could give different effect on reactivity.